Mid2 Is a Putative Sensor for Cell Integrity Signaling in Saccharomyces cerevisiae - Rajavel, Mathumathi (American Society for Microbiology, 1999)
Hcs77 is a putative cell surface sensor for cell integrity signaling in Saccharomyces cerevisiae. Its loss of function results in cell lysis during growth at elevated temperatures (e.g., 39°C) and impaired signaling to the Mpk1 mitogen-activated protein kinase in response to mild heat shock. We isolated the MID2 gene as a dosage suppressor of the cell lysis defect of an hcs77 null mutant. MID2 encodes a putative membrane protein whose function is required for survival of pheromone treatment. Mid2 possesses properties similar to those of Hcs77, including a single transmembrane domain and a long region that is rich in seryl and threonyl residues. We demonstrate that Mid2 is required for cell integrity signaling in response to pheromone. Additionally, we show that Mid2 and Hcs77 serve a redundant but essential function as cell surface sensors for cell integrity signaling during vegetative growth. Both proteins are uniformly distributed through the plasma membrane and are highly O-mannosylated on their extracellular domains. Finally, we identified a yeast homolog of MID2, designated MTL1, which provides a partially redundant function with MID2 for cell integrity signaling during vegetative growth at elevated temperature but not for survival of pheromone treatment. We conclude that Hcs77 is dedicated to signaling cell wall stress during vegetative growth and that Mid2 participates in this signaling, but its primary role is in signaling wall stress during pheromone-induced morphogenesis.